Data assimilation by the variational method with results for the Indian region - ANDERSSON, ERIK; KELLY, GRAEME A.; LANZINGER, ANDREAS (MAUSAM, 1997)
ABSTRACT. The variational method for data assimilation as implemented in the operational scheme at ECMWF is briefly presented. The performance of the variational scheme (3D-Var) with respect to tropical cyclones and the Asian summer monsoon is investigated and compared to the Optimum Interpolation scheme. It is found that the analysis of near-surface winds has improved significantly particularly in the vicinity of tropical storms and depressions. The better analyses have led to improvements in the short range forecasts (day 1 to day 3) of such systems. The summer monsoon appears slightly stronger in the 3D-Var analyses, giving enhanced forecast precipitation over the Western Ghats and over large parts of northern India. Only in the latter of these two areas does this verify with observations. The forecasts for India of geopotential, wind and temperature have improved significantly at all forecast ranges, as verified against own analyses. These results are based on 28 cases in two separate 2-week periods.